PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASA PASIEN RAWAT JALAN DI RSUD SELASIH KABUPATEN PELALAWAN - Sarah azhari, Mey; Salim, Agus (LPPM Universitas Awal Bros, 2022)
Service quality can be used as an indicator as a measure of customer satisfaction with a company. Satisfaction is the occurrence of feelings of pleasure or disappointment towards someone that arises after comparing performance such as product results that are thought to performance or getting an expected result. This study aims to determine the effect of service quality on outpatient satisfaction at RSUD Selasih, Pelalawan Regency. This study uses a quantitative research method with a descriptive approach, carried out at RSUD Selasih, Pelalawan Regency with a total of 67 samples of respondents. This research was carried out using observation data collection techniques and questionnaires. Data analysis used analysis of validity test, reliability test, univariate, bivariate, normality test and simple linear test. The results of the study of the quality of patient care, many chose to agree on each indicator, namely, thanibel, reliability, responsiveness, assurance, empathy, so patients were satisfied with the quality of service at Selasih Hospital, Pelalawan Regency. The results of patient satisfaction testing, patients are satisfied with the services provided at Selasih Hospital, Pelalawan Regency. Therefore, the quality of service affects patient satisfaction. From the test results, the patient was satisfied with the quality of service provided by the RSUD Selasih, Pelalawan Regency. The influence of service quality on outpatient satisfaction at Selasih Hospital, Pelalawan Regency.